2022-RA-1392-ESGO Tisotumab vedotin combinations with pembrolizumab or carboplatin in patients with recurrent/metastatic cervical cancer: interim results of ENGOT Cx8/GOG-3024/innovaTV205. (20th October 2022) - Lorusso, Domenica; Vergote, Ignace; O'Cearbhaill, Roisin E; Westermann, Anne M; Banerjee, Susana; van Nieuwenhuysen, Els; Iglesias, David A; Collins, Dearbhaile; Cibula, David; Madsen, Kristine; Tewari, Krishnansu S; Pignata, Sandro; et al.
Abstract : Introduction/Background: Pembrolizumab + chemotherapy as first-line (1L) and tisotumab vedotin (TV) monotherapy as second-line plus (2L+) have improved outcomes in patients with recurrent/metastatic cervical cancer (r/mCC). Previous reports show potentially enhanced efficacy and tolerable safety with TV + pembrolizumab, carboplatin, or bevacizumab. We report interim safety and efficacy results from the dose-expansion cohorts evaluating 1L TV + pembrolizumab (1L-TP), 2/3L TV + pembrolizumab (2/3L-TP), and 1L TV + carboplatin (1L-TC) in patients with r/mCC. Methodology: In the 1L-TP cohort, patients with r/mCC who had no prior systemic therapy (excluding chemoradiation) received TV 2.0 mg/kg + pembrolizumab 200 mg IV Q3W. In the 2/3L-TP cohort, patients with r/mCC who experienced disease progression on/after 1–2 prior systemic therapies received TV 2.0 mg/kg + pembrolizumab 200 mg IV Q3W. In the 1L-TC cohort, patients with r/mCC who had no prior systemic therapy (excluding chemoradiation) received TV 2.0 mg/kg + carboplatin AUC 5 IV Q3W. The primary end point was confirmed objective response rate (cORR) per RECIST v1.1. Results: In the 1L-TP, 2/3L-TP, and 1L-TC cohorts, respectively, 33, 35, and 33 patients received treatment, and, at data cut-off, median follow-up was 18.8, 15.0, and 14.6 months. cORR was 41%, 38%, and 55%, with a median DOR of not reached, 14.0, and 8.6 months in the 1L-TP, 2/3L-TP, and 1L-TC cohorts, respectively. Adverse events (AEs) of special interest in patients in the 1L-TP, 2/3L-TP, and 1L-TC cohorts (grade 1–2/grade ≥3) included ocular events (58/9; 51/3; 58/9), bleeding (61/6; 61/9; 52/6), and peripheral neuropathy (49/3; 37/3; 48/12), respectively; one patient in 2/3L-TP and one patient in 1L-TP experienced grade 4 and 5 treatment-related bleeding, respectively. Additional data will be presented at the meeting. Conclusion: TV + pembrolizumab or carboplatin in patients with r/mCC demonstrated encouraging and durable anti-tumour activity, with tolerable safety profiles. © 2022 American Society of Clinical Oncology, Inc. Reused with permission. This abstract was accepted and previously presented at the 2022 ASCO Annual Meeting. All rights reserved.